A method for alkali-activated solidification of sulfur-containing uranium waste rock and solidified body of sulfur-containing uranium waste rock prepared by the method

By using mineral powder, metakaolin and sodium silicate as alkali-activated gelling materials to treat sulfur-containing uranium waste rocks, forming stable solid block substances, solving the problems of high cost of traditional curing treatment and low early strength, and achieving economical and Environmentally friendly curing effect and reduce radioactive activity, suitable for environmentally friendly and building utilization.

CN117401956BActive Publication Date: 2024-12-17BEIJING RESEARCH INSTITUTE OF CHEMICAL ENGINEERING AND METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311432679.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2024-12-17
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The prior art has high curing cost and low early strength when dealing with sulfur-containing uranium waste stone, which is difficult to effectively prevent uranium release and environmental pollution, and there is a lack of research on alkali-exciting curing technology.

Method used

Ore powder, metakaolin and sodium silicate are used as alkali-excited gelling materials, and sulfur-containing uranium waste stone is mixed with river sand, and after molding and curing, a stable solid block substance is formed to replace traditional cement curing.

Benefits of technology

It has achieved economical, environmentally friendly and safe curing treatment. The cured body has good compressive strength, freezing and impact resistance, low radioactive activity, complies with environmental protection regulations, and is suitable for landfill or as a building material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117401956B_ABST
    Figure CN117401956B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of pollutant removal. The present invention provides a method for alkali-activated solidification of sulfur-containing uranium waste rock and a solidified body of sulfur-containing uranium waste rock prepared therefrom; the sulfur-containing uranium waste rock, river sand and water are mixed to obtain a first mixture; the first mixture, a cementitious material and water are mixed to obtain a second mixture; the second mixture and water are mixed and then molded, allowed to stand and cured in sequence to obtain a solidified body of sulfur-containing uranium waste rock; the cementitious material comprises mineral powder, metakaolin and sodium silicate in a mass ratio of 3.0 to 3.4: 0.7 to 0.9: 0.9 to 1.1. The solidified body of sulfur-containing uranium waste rock of the present invention has good compressive strength, antifreeze performance and impact resistance, has no obvious cracks or fissures after long-term immersion in water, and has good resistance to water immersion; the uranium concentration of the acid leaching solution does not exceed 5.30ug / L; the radioactivity concentration of the solidified body of sulfur-containing uranium waste rock is lower than 0.4Bq / cm 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pollutant removal, and in particular to a method for alkali-activated solidification of sulfur-containing uranium waste rock and a solidified body of sulfur-containing uranium waste rock prepared therefrom. Background Art

[0002] Sulfur-containing uranium waste rock refers to abandoned uranium ore containing sulfides or other waste generated during uranium processing. Sulfur-containing uranium waste rock mainly comes from the processing of uranium ore. During the extraction and concentration of uranium ore, a large amount of waste rock is produced, part of which contains sulfur and uranium. It has the following hazards: (1) Acidic emissions: When sulfur-containing uranium waste rock comes into contact with air, sulfides will oxidize into sulfuric acid. Sulfuric acid is a strong acid that may cause the formation of acid rain, damage the ecosystem of soil and water bodies, and affect plant growth; acidic emissions may also corrode infrastructure and buildings. (2) Radioactive contamination: Uranium is a radioactive element, and radioactive substances in sulfur-containing uranium waste rock may release radiation. Long-term exposure to radioactive substances may have an impact on human health. (3) Water pollution: Sulfuric acid in sulfur-containing uranium waste rock can form acidic water bodies after dissolving in water, polluting groundwater and water bodies, which poses a threat to the ecosystem and water supply resources and affects the health of aquatic organisms and humans. (4) Odor and dust: Sulfur-containing uranium waste rock may emit irritating odor and dust, which may have a negative impact on the health and comfort of surrounding residents.

[0003] In order to mitigate the hazards of sulfur-containing uranium waste rock, appropriate treatment and management measures should be taken, including the use of environmentally friendly technologies for waste treatment, limiting the spread of radioactive materials and sulfuric acid, and monitoring and supervising the environmental impact of waste treatment. In addition, the protection of workers engaged in the treatment of sulfur-containing uranium waste rock and surrounding residents should be strengthened to ensure their safety and health. Disposal methods for sulfur-containing uranium waste rock generally include the following: (1) Safe storage: The sulfur-containing uranium waste rock is sealed in specially designed safe storage facilities to ensure its safe long-term storage. These facilities need to have the ability to prevent radiation leakage and environmental pollution, and the cost is very high. (2) Solidification treatment: The sulfur-containing uranium waste rock is mixed with an appropriate solidifying agent to form a solid block material to reduce the risk of its dissolution and release. These solid blocks can be stored and disposed of more easily. (3) Underground storage: The sulfur-containing uranium waste rock is buried in a specially designed storage facility deep underground. This method can reduce radiation, but this method is large in engineering and consumes a lot of manpower and material resources. Solidification treatment is an economical and convenient technology. Currently, cement solidification technology is mainly used. When ordinary Portland cement is used as the cementitious material, the filling body often has low early strength and high cost.

[0004] There are few reports on the treatment technology of alkali-activated solidification of sulfur-containing uranium waste rock. Therefore, it is of great significance to study a method for solidifying sulfur-containing uranium waste rock using mineral powder and sodium silicate as alkali-activated cementitious materials. Summary of the invention

[0005] The purpose of the present invention is to provide a method for alkali-activated solidification of sulfur-containing uranium waste rock and a solidified body of sulfur-containing uranium waste rock prepared therefrom in order to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for alkali-activated solidification of sulfur-containing uranium waste rock, comprising the following steps:

[0008] 1) mixing sulfur-containing uranium waste rock, river sand and water to obtain a first mixture;

[0009] 2) mixing the first mixture, a gelling material and water to obtain a second mixture;

[0010] 3) mixing the second mixture with water, and then sequentially performing molding, standing, and curing to obtain a solidified body of sulfur-containing uranium waste rock;

[0011] Step 2) The cementitious material comprises mineral powder, metakaolin and sodium silicate, and the mass ratio of the mineral powder, metakaolin and sodium silicate is 3.0-3.4:0.7-0.9:0.9-1.1.

[0012] Preferably, in step 1), the mass ratio of the sulfur-containing uranium waste rock, river sand and water is 0.4-1.0:1.0-1.6:0.15-0.19.

[0013] Preferably, the particle size of the sulfur-containing uranium waste rock in step 1) is 0.1-1.6 mm, wherein the mass ratio of the sulfur-containing uranium waste rock with a particle size of 0.1-1.25 mm to the sulfur-containing uranium waste rock with a particle size of 1.25-1.6 mm is 1-2:1-2.

[0014] Preferably, the mass ratio of the cementitious material to water in step 2) is 0.9-1.1:0.15-0.19; the mass ratio of the cementitious material to the river sand in step 1) is 0.9-1.1:1.0-1.6.

[0015] Preferably, the mass ratio of the water in step 3) to the river sand in step 1) is 0.15-0.19:1.0-1.6.

[0016] Preferably, the mixing time in step 1) is 30 to 50 seconds, the mixing time in step 2) is 20 to 40 seconds, and the mixing time in step 3) is 110 to 130 seconds.

[0017] Preferably, in step 3), the molding time is 320 to 400 seconds, and the standing time is 45 to 52 hours.

[0018] Preferably, in step 3), the curing temperature is 22-28° C., the curing humidity is 94-98%, and the curing time is 26-30 days.

[0019] The present invention also provides a sulfur-containing uranium waste rock solidified body prepared by the method for alkali-activated solidification of sulfur-containing uranium waste rock.

[0020] The beneficial effects of the present invention include:

[0021] 1) The present invention uses mineral powder, metakaolin and sodium silicate as cementitious materials, which are more economical, environmentally friendly and convenient. River sand and sulfur-containing uranium waste rock are used as fine aggregates. The sulfur-containing uranium waste rock is mixed, molded and cured with the cementitious materials to form a stable solid block material to prevent uranium from being released into the environment and minimize waste. Alkali-activated cementitious materials are used to replace traditional cement solidification, which is more economical, safe and stable.

[0022] 2) The solidified sulfur-containing uranium waste rock of the present invention has good compressive strength, antifreeze performance and impact resistance. It has no obvious cracks or fissures after long-term immersion in water. The loss of compressive strength after immersion in water is small, and it has good resistance to water immersion. The uranium concentration of the acid leaching solution is low. The radioactivity concentration of the solidified sulfur-containing uranium waste rock is lower than 0.4Bq / cm 2 ; It complies with the "Regulations on Radiation Protection and Environmental Protection in Uranium Mining and Metallurgy" (GB23727-2020). The solidified sulfur-containing uranium waste rock of the present invention can be landfilled or used as a building material to ensure its safety and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram of the compressive strength of the solidified sulfur-containing uranium waste rock obtained by different doping amounts of the sulfur-containing uranium waste rock in Examples 1, 4 to 6 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0024] The present invention provides a method for alkali-activated solidification of sulfur-containing uranium waste rock, comprising the following steps:

[0025] 1) mixing sulfur-containing uranium waste rock, river sand and water to obtain a first mixture;

[0026] 2) mixing the first mixture, a gelling material and water to obtain a second mixture;

[0027] 3) mixing the second mixture with water, and then sequentially performing molding, standing, and curing to obtain a solidified body of sulfur-containing uranium waste rock;

[0028] Step 2) The cementitious material comprises mineral powder, metakaolin and sodium silicate, and the mass ratio of the mineral powder, metakaolin and sodium silicate is 3.0-3.4:0.7-0.9:0.9-1.1.

[0029] In the present invention, the mass ratio of the sulfur-containing uranium waste rock, river sand and water in step 1) is preferably 0.4-1.0:1.0-1.6:0.15-0.19, more preferably 0.5-0.8:1.2-1.5:0.16-0.18, and more preferably 0.6-0.7:1.3-1.4:0.17.

[0030] In the present invention, the particle size of the sulfur-containing uranium waste rock in step 1) is preferably 0.1-1.6 mm, wherein the mass ratio of the sulfur-containing uranium waste rock with a particle size of 0.1-1.25 mm (including 0.1 mm and excluding 1.25 mm) to the sulfur-containing uranium waste rock with a particle size of 1.25-1.6 mm (including 1.25 mm and 1.6 mm) is preferably 1-2:1-2, and more preferably 1:1.

[0031] In the present invention, the mass ratio of the cementitious material and water in step 2) is preferably 0.9-1.1:0.15-0.19, more preferably 0.95-1.05:0.16-0.18, and more preferably 1.0:0.17; the mass ratio of the cementitious material and the river sand in step 1) is preferably 0.9-1.1:1.0-1.6, more preferably 0.95-1.05:1.2-1.5, and more preferably 1.0:1.3-1.4.

[0032] In the present invention, the mass ratio of mineral powder, metakaolin and sodium silicate is preferably 3.1-3.3:0.75-0.85:0.95-1.05, and more preferably 3.2:0.8:1.0.

[0033] In the present invention, the sodium silicate is solid sodium silicate, and the modulus of the sodium silicate is preferably 1.8 to 2.2, more preferably 1.9 to 2.1, and more preferably 2.0.

[0034] In the present invention, the mass ratio of the water in step 3) to the river sand in step 1) is preferably 0.15-0.19:1.0-1.6, more preferably 0.16-0.18:1.2-1.5, and more preferably 0.17:1.3-1.4.

[0035] In the present invention, the mixing time in step 1) is preferably 30 to 50 seconds, more preferably 35 to 45 seconds, and more preferably 40 seconds; before the mixing, the sulfur-containing uranium waste rock is preferably mixed first, and the mixing time of the sulfur-containing uranium waste rock is preferably 15 to 25 seconds, more preferably 17 to 22 seconds, and more preferably 20 seconds.

[0036] In the present invention, the mixing time in step 2) is preferably 20 to 40 s, more preferably 25 to 35 s, and more preferably 30 s; the mixing time in step 3) is preferably 110 to 130 s, more preferably 115 to 125 s, and more preferably 120 s.

[0037] In the present invention, the molding time in step 3) is preferably 320 to 400 s, and the molding is preferably carried out sequentially by compaction molding on a compaction table and vibration molding on a vibration table; the compaction molding time is preferably 220 to 260 s, more preferably 230 to 250 s, and more preferably 240 s; the vibration molding time is preferably 100 to 140 s, more preferably 110 to 130 s, and more preferably 120 s.

[0038] In the present invention, after the molding is completed, a molded product is obtained, and the molded product is sequentially placed and cured.

[0039] In the present invention, the standing time in step 3) is preferably 45 to 52 hours, more preferably 47 to 50 hours, and more preferably 48 to 49 hours; during the standing process, it is preferred to spray water on the surface of the molded product until the surface is moistened after standing for 23 to 25 hours, and it is further preferred to spray water on the surface of the molded product until the surface is moistened after standing for 24 hours.

[0040] In the present invention, too short a standing time results in an incomplete molded product.

[0041] In the present invention, the curing temperature in step 3) is preferably 22 to 28°C, more preferably 24 to 27°C, and more preferably 25 to 26°C; the curing humidity is preferably 94 to 98%, more preferably 95 to 97%, and more preferably 96%; the curing time is preferably 26 to 30 days, more preferably 27 to 29 days, and more preferably 28 days.

[0042] The present invention also provides a sulfur-containing uranium waste rock solidified body prepared by the method for alkali-activated solidification of sulfur-containing uranium waste rock.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] In the embodiment, the planetary cement mortar mixer is a JJ-5 type planetary cement mortar mixer;

[0045] S95 mineral powder SiO 2 The content is 33%, Al 2 O 3 The content is 15%; the particle size of river sand is 0.1-1mm;

[0046] Vibration table: ZH·DG-80, Wuxi Jianyi Instrument Machinery Co., Ltd., vibration frequency 60 times / min; compaction table: ZT-95, Hebei Kexi Instrument Equipment Co., Ltd., vibration frequency 60 times / min.

[0047] Example 1

[0048] 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm and 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm were poured into a planetary cement mortar mixer and stirred at a rate of 60 r / min for 20 seconds; then 1.4 kg of river sand and 0.17 kg of water were added and stirred at a rate of 60 r / min for 40 seconds to obtain a first mixture. 1.0 kg of cementitious material (in the cementitious material, the mass ratio of S95 mineral powder, metakaolin and solid sodium silicate is 3.2:0.8:1.0) and 0.17 kg of water were added to the planetary cement mortar mixer and stirred at a rate of 60 r / min for 30 seconds; finally 0.17 kg of water was added and stirred rapidly at a rate of 200 r / min for 120 seconds to obtain a mixture. The modulus of solid sodium silicate is 2.0.

[0049] The mixture was injected into a cylindrical mold of φ50mm×50mm, first compacted with a vibrating table for 240s, then vibrated with a vibration table for 120s, and then placed at room temperature. After 24h, water was sprayed on the surface of the molded product until the surface was moistened. After the placement time reached 48h, the mold was demoulded. When demoulding, the upper end of the mold was first knocked with a hammer to separate the solidified body from the mold surface. After demoulding, the solidified body was placed in a standard constant temperature and humidity curing box for curing at a temperature of 25°C and a humidity of 96% for 28 days to obtain a solidified body of sulfur-containing uranium waste rock.

[0050] Example 2

[0051] 0.25 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm and 0.25 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm were poured into a planetary cement mortar mixer and stirred at a rate of 60 r / min for 17 seconds; 1.5 kg of river sand and 0.16 kg of water were added and stirred at a rate of 60 r / min for 35 seconds to obtain a first mixture. 0.9 kg of cementitious material (in the cementitious material, the mass ratio of S95 mineral powder, metakaolin and solid sodium silicate is 3.1:0.75:1.05) and 0.16 kg of water were added to the planetary cement mortar mixer and stirred at a rate of 60 r / min for 25 seconds; finally, 0.16 kg of water was added and stirred rapidly at a rate of 200 r / min for 115 seconds to obtain a mixture. The modulus of solid sodium silicate is 1.9.

[0052] The mixture was injected into a cylindrical mold of φ50mm×50mm, first compacted with a vibrating table for 230s, then vibrated with a vibration table for 110s, and then placed at room temperature. After 23h, water was sprayed on the surface of the molded product until the surface was moistened. After the placement time reached 47h, the mold was demoulded. When demoulding, the upper end of the mold was first knocked with a hammer to separate the solidified body from the mold surface. After demoulding, the solidified body was placed in a standard constant temperature and humidity curing box for curing at a temperature of 22°C and a humidity of 95% for 28 days to obtain a solidified body of sulfur-containing uranium waste rock.

[0053] Example 3

[0054] 0.35 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm and 0.35 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm were poured into a planetary cement mortar mixer and stirred at a rate of 60 r / min for 22 seconds; 1.3 kg of river sand and 0.18 kg of water were added and stirred at a rate of 60 r / min for 45 seconds to obtain a first mixture. 1.1 kg of cementitious material (in the cementitious material, the mass ratio of S95 mineral powder, metakaolin and solid sodium silicate is 3.3:0.85:0.95) and 0.18 kg of water were added to the planetary cement mortar mixer and stirred at a rate of 60 r / min for 35 seconds; finally, 0.18 kg of water was added and stirred rapidly at a rate of 200 r / min for 125 seconds to obtain a mixture. The modulus of solid sodium silicate is 2.1.

[0055] The mixture was injected into a cylindrical mold of φ50mm×50mm, first compacted with a vibrating table for 250s, then vibrated with a vibration table for 130s, and then placed at room temperature. After 25h, water was sprayed on the surface of the molded product until the surface was moistened. After the placement time reached 49h, the mold was demoulded. When demoulding, the upper end of the mold was first knocked with a hammer to separate the solidified body from the mold surface. After demoulding, the solidified body was placed in a standard constant temperature and humidity curing box for curing at a temperature of 27°C and a humidity of 97% for 28 days to obtain a solidified body of sulfur-containing uranium waste rock.

[0056] Example 4

[0057] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.4 kg of river sand in Example 1 were replaced with 0.2 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.2 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.6 kg of river sand. Other conditions are the same as in Example 1.

[0058] Example 5

[0059] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.4 kg of river sand in Example 1 were replaced with 0.4 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.4 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.2 kg of river sand, and the other conditions were the same as in Example 1.

[0060] Example 6

[0061] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.4 kg of river sand in Example 1 were replaced with 0.5 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.5 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.0 kg of river sand. Other conditions are the same as in Example 1.

[0062] Comparative Example 1

[0063] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.4 kg of river sand in Example 1 were replaced with 0.7 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.7 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 0.6 kg of river sand, and the other conditions were the same as in Example 1.

[0064] Comparative Example 2

[0065] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and 1.4 kg of river sand in Example 1 were replaced with 1.0 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, and 1.0 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and the other conditions were the same as in Example 1.

[0066] Comparative Example 3

[0067] The 0.3 kg of sulfur-containing uranium waste rock with a particle size of 0.1 to 1.25 mm, the 0.3 kg of sulfur-containing uranium waste rock with a particle size of 1.25 to 1.6 mm, and the 1.4 kg of river sand in Example 1 were changed to 2 kg of river sand, and the other conditions were the same as in Example 1.

[0068] The solidified sulfur-containing uranium waste rock of Examples 1 to 6 was vertically and freely dropped from a height of 9 m onto a concrete floor. Only small fragments appeared on the edges and corners of the test blocks, but they were not broken, and had good impact resistance.

[0069] Tap water immersion test: The solidified bodies of sulfur-containing uranium waste rock of Examples 1 to 6 were immersed in tap water for 42 days respectively. There were no obvious cracks or fissures on the surface of the solidified bodies, and they had good water immersion resistance. The solidified bodies immersed in tap water were dried at room temperature for 3 days for compressive strength test. The compressive strength of the solidified body of Example 1 before immersion was 24.5MPa, and the compressive strength after immersion and drying was 21.7MPa. The compressive strength after immersion can still reach more than 88% of that before immersion.

[0070] Acid leaching test: Mix concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: AR, mass concentration 95%, concentrated nitric acid: AR, mass concentration 95%) in a mass ratio of 2:1 to obtain a concentrated acid mixture, add the concentrated acid mixture to water (add 2 drops of the mixture to 1L of water), and the pH value of the prepared acid leaching solution is 3.21. 100g of the solidified sulfur-containing uranium waste rock of Examples 1 to 3 was crushed through a 3mm sieve to obtain a crushed body and mixed with 1L of acid leaching solution, respectively, and oscillated in a horizontal oscillation device at a speed of 110r / min at room temperature for 8h, and then allowed to stand for 16h to filter the leaching solution. The pH value of the leaching solution of Example 1 is 11.11, and the uranium concentration in the leaching solution is 5.30ug / L; the uranium concentration in the leaching solution of Example 2 is 5.32ug / L; the uranium concentration in the leaching solution of Example 3 is 5.35ug / L.

[0071] Surface contamination test: The β surface radioactivity concentration of the sulfur-containing uranium waste rock raw material in Example 1 is 4.58 Bq / cm 2 , the solidified body of sulfur-containing uranium waste rock is 0.35Bq / cm 2 The β surface radioactivity concentration of the sulfur-containing uranium waste rock raw material in Example 2 is 4.65 Bq / cm 2 , the solidified body of sulfur-containing uranium waste rock is 0.37Bq / cm 2 The β surface radioactivity concentration of the sulfur-containing uranium waste rock raw material in Example 3 is 4.55 Bq / cm 2 , the solidified body of sulfur-containing uranium waste rock is 0.34Bq / cm 2 The alkali-activated solidification method of sulfur-containing uranium waste rock of the present invention can significantly reduce its radiation level.

[0072] Freeze-thaw cycle test: The solidified bodies of sulfur-containing uranium waste rock of Examples 1 to 3 were frozen in a -20°C freezer for 3 hours, then taken out and thawed in 20°C water, and the freeze-thaw cycle test was repeated 5 times before the solidified bodies were subjected to a freeze resistance test. The results showed that the appearance of the solidified bodies of sulfur-containing uranium waste rock did not change significantly, and the compressive strength losses of the solidified bodies of Examples 1 to 3 were 25%, 27%, and 28%, respectively.

[0073] The compressive strength of the solidified bodies of sulfur-containing uranium waste rock obtained by different dosages of sulfur-containing uranium waste rock in Examples 1, 4 to 6 and Comparative Examples 1 to 3 is as follows: Figure 1 As shown. Figure 1It can be seen that when the sulfur-containing uranium waste rock in the fine aggregate (the mass of sulfur-containing uranium waste rock and river sand) is 20% (Example 4), the compressive strength of the solidified body is the best, which is 25.1MPa. When the sulfur-containing uranium waste rock in the fine aggregate is 50% (Example 6), the compressive strength of the solidified body is 21.2MPa, which is close to the optimal compressive strength, with a difference of 3.9MPa. The compressive strength of the solidified body obtained by solidifying the sulfur-containing uranium waste rock with C35 cement (the cementitious material in Example 1 is replaced with C35 cement of equal mass, and other conditions are the same as Example 1) for 28 days is 10.8MPa.

[0074] The solidified sulfur-containing uranium waste rock of the present invention has good compressive strength, antifreeze performance and impact resistance, has no obvious cracks or fissures after long-term immersion in water, has little loss of compressive strength after immersion in water, and has good resistance to water immersion; the uranium concentration of the acid leaching solution does not exceed 5.30ug / L; the radioactivity concentration of the solidified sulfur-containing uranium waste rock is lower than 0.4Bq / cm 2 ; It complies with the "Regulations on Radiation Protection and Environmental Protection in Uranium Mining and Metallurgy" (GB23727-2020); The method of the present invention can effectively improve the utilization rate of solid waste.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for solidifying sulfur-containing uranium waste rock by alkali activation, characterized in that: The following steps are included: 1) mixing sulfur-containing uranium waste rock, river sand and water to obtain a first mixture; 2) mixing the first mixture, a gelling material and water to obtain a second mixture; 3) mixing the second mixture with water, and then sequentially performing molding, standing, and curing to obtain a solidified body of sulfur-containing uranium waste rock; Step 2) the gelling material comprises mineral powder, metakaolin and sodium silicate, the mass ratio of mineral powder, metakaolin and sodium silicate is 3.0-3.4:0.7-0.9:0.9-1.1; the sodium silicate is solid sodium silicate; Step 1) The mass ratio of the sulfur-containing uranium waste rock, river sand and water is 0.4-1.0:1.0-1.6:0.15-0.19; Step 1) The particle size of the sulfur-containing uranium waste rock is 0.1-1.6 mm, wherein the mass ratio of the sulfur-containing uranium waste rock with a particle size of 0.1-1.25 mm to the sulfur-containing uranium waste rock with a particle size of 1.25-1.6 mm is 1-2:1-2; The mass ratio of the gelling material to water in step 2) is 0.9-1.1:0.15-0.19; the mass ratio of the gelling material to the river sand in step 1) is 0.9-1.1:1.0-1.

6.

2. The method according to claim 1, characterized in that The mass ratio of the water in step 3) to the river sand in step 1) is 0.15-0.19:1.0-1.

6.

3. The method according to claim 1 or 2, characterized in that: The mixing time in step 1) is 30 to 50 seconds, the mixing time in step 2) is 20 to 40 seconds, and the mixing time in step 3) is 110 to 130 seconds.

4. The method according to claim 3, characterized in that Step 3) The molding time is 320 to 400 seconds, and the standing time is 45 to 52 hours.

5. The method according to claim 4, characterized in that Step 3) The curing temperature is 22-28° C., the curing humidity is 94-98%, and the curing time is 26-30 days.

6. The solidified body of sulfur-containing uranium waste rock prepared by the method for alkali-activated solidification of sulfur-containing uranium waste rock according to any one of claims 1 to 5.